Point prevalence of healthcare-associated infections and antibiotic use in three large Swiss acute-care hospitals - Aliki Metsini; Miriam Vazquez; Rami Sommerstein; Jonas Marschall; Cathy Voide; Nicolas Troillet; Céline Gardiol; Didier Pittet; Walter Zingg; the Swissnoso network (Swiss Medical Weekly, 2018)
BACKGROUND